Copulas and portfolios in the electric vehicle sector - Andrej Stenšin; Daumantas Bloznelis (Journal of Risk and Financial Management, 2022)
How can investors unlock the returns on the electric vehicle industry? Available investment choices range from individual stocks to exchange traded funds. We select six representative assets and characterize the time-varying joint distribution of their returns by copula-GARCH models. They facilitate portfolio optimization targeted at a chosen combination of risk and reward. With daily data from 2012 to 2020, we illustrate the models' applicability by building a minimum expected shortfall portfolio and comparing its performance to that of an equally weighted benchmark. Our results should be of interest to investors and risk managers seeking or facing exposure to the electric vehicle sector.
Keywords: G11; G17; C58; Q02; 330; portfolio optimization; electric vehicles; copula; vines; expected shortfall; value-at-risk